Diplomacy - Berridge, G. R. author. aut Link
XVI, 296 p.
Keywords: Fully revised and updated, this comprehensive guide to diplomacy explores the art of negotiating international agreements and the channels through which such activities occur when states are in diplomatic relations, and when they are not. This new edition includes chapters on secret intelligence and economic and commercial diplomacy.